Asia's transition to net zero: Opportunities and challenges in agriculture - Architesh Panda; Takashi Yamano (Asian Development Bank (ADB), 2023)
Asia is home to 60% of the world's population, 52% of global agricultural production, and 43% of agriculture-related greenhouse gas (GHG) emissions. While a large portion of the Asian population depends on agriculture for their livelihood and food security, the agriculture sector is one of the main sources of GHG emissions in the region. In some Asian economies, it accounts for more than 40% of total emissions. This report identifies the major sources of GHG emissions from the agriculture sector and reviews a variety of tools and technologies to change emission pathways. It also discusses the institutional, political, and economic challenges for achieving progress toward a cost-effective, inclusive, and resilient transition to net-zero agriculture.
Keywords: Q01; Q1; Q54; 330; climate change; net-zero agriculture; Asia and the Pacific; non-carbon dioxide equivalent; non-CO2e